CHITOSAN BEADS WITH MAGNETICS PARTICLES AND THEIR APPLICATION IN THE ADSORPTION OF IONS Cu (II) - Tapia H., N. (2012)
The objective of this work is to prepare chitosan beads with magnetic properties for use in the adsorption of Cu (II). Through a process reported in the literature have been obtained with micro chitosan beads magnetite particles of2,5 mm diameter in the wet state and diameter of 0,8 mm when dry. Subsequently chitosan beads adsorption used for Cu (II), in a batch system, determining which optimum pH is in the range of 4.7 to 5.2. The study of the kinetics of the adsorption process showed that thermodynamic equilibrium is attained 250 min before starting the process. The experimental data described adsorption by the Langmuir model and found that the maximum adsorption capacity is qmax = 235,84 mg/g constant value Langmuir, b = 0,00442